GAMBARAN DARAH AYAM PETELUR FASE GROWER (7--10 MINGGU) PADA KEPADATAN KANDANG BERBEDA - Wijayanti, Dewi; Hartono, Madi; ., Riyanti (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
The research aimed to determine the hematological profile (erythrocytes, leukocytes, andhemoglobin) of grower laying hens with different cage density and the best cage density. Thisresearch has been conducted in April 2014 using 210 grower laying hens 7--10 weeks in Varia AgungJaya Farm and Balai Veteriner Lampung. The treatment is given based on completely randomizeddesign (CRD), consisting of four treatments and five replications. The data was analyzed usinganalysis of variance on 5% significance level.The result of the research shows that the density of the cage 6,9,12, and 15 hens m-2 have notsignificant (P>0,05) on hematological profile (erythrocytes 1,04--2,74 x 106 mm-3; leukocytes 27,96--52,52 x 103 mm-3; and hemoglobin 6,40--8,20 g/dl).